ANALISIS HUBUNGAN PENDIDIKAN MULTIKULTURAL DAN PENDIDIKAN INKLUSI - Delfiana Putri, Ditta; Zakiah, Linda; Azzahra, Fatimah; Ayu Ningsih, Litha; Jaya, Indra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to (1) explain the concepts of multicultural education and inclusive education (2) analyze the relationship between multicultural education and inclusive education. This type of research is library research which is descriptive qualitative in nature. The data analysis technique is content analysis. The results of this research show that multicultural education is education that emphasizes the process of cultivating a way of life that is mutually respectful, sincere and tolerant of cultural diversity living in a society with a high level of plurality. This concept is in line with the concept of inclusive education, namely an educational process that provides opportunities for all children by prioritizing aspects of personal, academic and professional development, including children with disabilities and special children without any distinction, to study in the same school environment. The relationship between multicultural education and inclusive education is in the form of disassociative social relations (contradiction) and associative social relations (accommodation). To support the success of this education, the National Education System Law and Minister of National Education Regulation No. 70 of 2009 must be implemented correctly and receive support from schools, communities and families.